COVID-19 Health Information-seeking Behavior in Timorese Society: A Phenomenological Study - Mas’amah; Juan Nafie; Christian J. Bale Lembang; Apris A. Adu; Sarci M. Toy; R. Pasifikus Christa Wijaya; Indra Yohanes Kiling (Institute of Medico-legal Publications Pvt Ltd, 2021)
This study aims to determine the media used in obtaining health information about COVID-19 and the reasons for choosing the media. The theory used is Information-seeking Behavior. This research is qualitative with the phenomenological method. The informants were 38 people who were selected based on the purposive sampling technique. Data collection was carried out utilizing in-depth interviews, observation, and documentation. The data analysis technique is Creswell’s data analysis in phenomenological research. The results showed that the media used to find health information about COVID-19 were printed mass media (newspapers, magazines, and tabloids), electronic media (television, radio), and internet media. Meanwhile, choosing the media was due to the ease of accessing existing media and the diversity of information obtained.